Вивчення якості пилку у абрикоса (Armeniaca vulgaris L.) та персика (Persica vulgaris Mill.) при інтродукції в Лісостепу України - Kudrenko, I.K.; Grynenko, N.S.; Moroz, P.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
For selection works quality of pollen of peach and apricot are determined. Is shown, that sterility at an apricot is determined not only origin, but also terms of maturing of the forms.